Private and public educational institutions in their preparation for admission to the UNMSM - Blanco Obregón, Jaziel Martin (2024)
The present work is the summary of the research carried out at the Universidad Nacional Mayor de San Marcos, where the objective was to determine the impact of the educational institution of origin; individual or state, in the performance for the admission exam, for which an instrument composed of three sections was developed: short questions, measurement scale type questions and the semi-structured interview. The instrument was applied, through 148 entrants to the National University of San Marcos in the period 2023 - II, the selection of the participants was through non-probabilistic free-hand sampling; Among the main findings, it was determined that there is a significant impact on those entering the UNMSM; Private educational institutions have a significant impact on the academic development of students, while state educational institutions have a privilege in soft skills and emotional intelligence; Therefore, these last new students are better prepared to face situations of stress, pressure or where persistence is needed.